Identification and Characterization of Potential Phenol Degrading Bacterial strains Isolated from Municipal Sewage, Bilaspur, Chhattisgarh - Parihar, Rashmi; Dubey, Sumit Kumar (International Journal of Applied Sciences and Biotechnology, 2016)
Phenol and its derivatives are consistently causing harmful effects to an aquatic ecosystem. The present study focused on the isolation and characterization of potential phenol degrading bacterial strains and subsequently optimization of media ingredients for efficient phenol degradation by potential bacterial strains. Bacterial strains were isolated from municipal sewage, Bilaspur (21'47 and 23'8 N 81'14 and 83'15 E). After optimization phenol degradation rate was increased by 1.84 fold for PDB 5 (from 40.37% to 74.67%) and 1.39 fold for PDB 11 (from 58.62% to 81.51%) at 500mg/l initial phenol concentration. PDB 5 and PDB 11 were identified as Streptococcus sp. PDB 5 and Pseudomonas sp. PDB 11 respectively as potential phenol degrading bacterial strains. These strains can further be used in microbially assisted phenol degradation to remove phenol derivatives present in industrial wastewater. Int J Appl Sci Biotechnol, Vol 4(3): 288-293